Analisis Kesalahan Siswa Kelas V MI dalam Mengerjakan Soal Matematika Materi Statistika - Maghfirotul Firmaning Lestari (Gunung Djati Conference Series, 2022)
This study aims to analyze the errors of class V Madrasah Ibtidaiyah students in doing math problems on statistical material. This research method is descriptive qualitative with assessment instruments through giving questions and interviews with teachers. The research was conducted using 19 students as the subject. The test questions given are in the form of two description questions. The results and discussion obtained from this study is that low student scores still dominate, based on the results of students in working on statistics questions, it can be found several errors caused by lack of understanding, lack of thoroughness, and also lack of understanding of the concept of statistics. Therefore, this can certainly be a reflection for teachers and prospective teachers so that later they can improve their learning system so that they can make students understand what is being conveyed.